2014
DOI: 10.11159/vwhci.2014.002
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Technology to Enhance Psychotherapy for Treatment of Schizophrenia: A Feasibility Study

Abstract: Forty-two experienced clinicians who work with consumers diagnosed with schizophrenia were surveyed in order to assess the feasibility of using mobile applications as an adjunct to conventional treatment. Clinicians reported that over two-thirds of their consumers could safely make use of this technology. In addition, a majority of consumers were seen as likely to benefit from all but one of the fifteen functions performed by the investigational app (TherAPPist).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Such a slow uptake of mHealth in schizophrenia might in part be due to assumptions that attend the illness, stigmatizing or otherwise, that include concerns about cognitive capacity, symptoms such as delusions, and poverty, and their implications for technology use. Such assumptions are increasingly being contrasted with findings that over 80% of individuals with schizophrenia and other psychoses routinely use cellphone technology without difficulty [9], with a majority expressing an interest in mHealth interventions [10]. Specific areas of interest for applications include reminders regarding medications, check-ins with practitioners, reminders about appointments, and psychoeducation [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a slow uptake of mHealth in schizophrenia might in part be due to assumptions that attend the illness, stigmatizing or otherwise, that include concerns about cognitive capacity, symptoms such as delusions, and poverty, and their implications for technology use. Such assumptions are increasingly being contrasted with findings that over 80% of individuals with schizophrenia and other psychoses routinely use cellphone technology without difficulty [9], with a majority expressing an interest in mHealth interventions [10]. Specific areas of interest for applications include reminders regarding medications, check-ins with practitioners, reminders about appointments, and psychoeducation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the academic literature, a recent review identified 11 studies of schizophrenia-specific mHealth applications [15], with our identifying 4 papers published since [1619]. These studies, and the broader literature that includes web-based platforms, suggest that the range of ehealth and mHealth approaches that include functions such as reminders, self-assessments, behavioural prompts, and in some instances cognitive remediation, are feasible with this population and do not result in any noted risks [10,15,1921]. Feasibility studies form the bulk of this small body of literature.…”
Section: Introductionmentioning
confidence: 99%
“…A number of pilot studies suggest that schizophrenia-targeted mobile and web-based apps in areas such as cognitive remediation are feasible and do not result in any noted risks [ 23 , 26 ]. Most directly relevant to this proposal is the work of Ben-Zeev and colleagues [ 27 ].…”
Section: Introductionmentioning
confidence: 99%